Bibliographic study of Spanish airports (1995-2015) through ISBN - Oliva Marañón, Carlos; Cejudo Mejías, Vanesa; Gallego Trijueque, Sara (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
Airports are a major infrastructure in all countries of the world. The objective of this research is to evaluate the scientific production of monographs on airports in Spain. Using the International Standard Book Number (ISBN), we examined the visibility of authors, scientific production by year, the notoriety of publishers and the geographical coverage of publications. The results show the existence of 119 documents classified by subject, the prevalence of the five-year period 2005-2009 by publications, the visibility of the AENA publishing house and the preeminence of the Community of Madrid as the headquarters of the publishers.